Potensi Hasil Beberapa Varietas Unggul Baru (VUB) Kedelai di Lahan Kering Sumatera Selatan - Renny Utami Somantri; Syahri Syahri; Tumarlan Thamrin (Seminar Nasional Lahan Suboptimal, 2018)
Somantri et al, 2019. Potential of Several Soybean Varieties in Dry Land of South Sumatera. pp. 473-481. Soybean productivity is determined by climate, land suitability also innovations applied such as the use of superior varieties.  Soybean cropping areas mostly covers ricefield and dry land in South Sumatera, in where rice field fertility is better than dry land.  With total of 364.583 Ha dry land, soybean cultivation is potential to be developed in South Sumatera to obtain self-sufficiency and minimize soybean imports.  The activity was carried out in Talang Ubi Sub-district in Penukal Abab Lematang Ilir (PALI) District in 2018.  The study was aimed to understand the growth and yield of some adaptive soybean superior varieties (VUB) in dry land of South Sumatera.  Technologies applied was the use of several soybean VUB i.e. Burangrang, Dering 1. Demas 1 dan Anjasmoro, fertilizer based on Dry Land Test Kit (PUTK), the use of manual grains seeder (ATBJ), Rhizobium application on seeds and integrated pest control. The result showed that the highest yield was obtained from Dering 1 for 2,3 t/ha of dry seed and the lowest was Burangrang for 1,36 t/ha.